For a geography of health approach in the population study: the cases of dengue distribution in Londrina, Paraná - Paula-Shinobu, Patrícia Fernandes; Silva, Lucas Fernando Bertacco da; Paula, Hugo Ribeiro Borges de (Geosaberes; Vol 9 No 17 (2018): Jan - Apr, 2017)
In the current article, we propose a activity about dengue and its distribution in Londrina, Paraná, with students of the 7th year of Paulo Freire State College. In the performance of the activity, a map of the dengue cases distribution, reports on the incidence of cases of the disease in the city and a map with the dispersion range of the female mosquito for egg deposit. All these languages resulted in the production of informative posters about dengue produced by students. The results showed that the approach of the Geography of Health in the studies about population made possible a better reading of the disease distribution by the students, who understood that the health conditions are influenced by the social, economic and political characteristics of each place
Keywords: Ensino de Geografia; Educação Ambiental; Geografia da Saúde; Percepção Abiental